2007
DOI: 10.1007/s00424-007-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

Permissive role of calcium on regulatory volume decrease in freshly isolated mouse cholangiocytes

Abstract: Calcium (Ca2+) pathways are important in cell volume regulation in many cells, but its role in volume regulatory processes in cholangiocytes is unclear. Thus, we have investigated the role of Ca2+ in regulatory volume decrease (RVD) in cholangiocytes using freshly isolated bile duct cell clusters (BDCCs) from normal mouse. No significant increase in [Ca2+]i was observed during RVD, while ionomycin and ATP showed significant increases. Confocal imaging also showed no significant changes in the levels or distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…This is consistent with previous reports that the activation of VRAC does not require an increase of intracellular Ca 2ϩ (37,77). However, there is considerable evidence that although elevation of Ca 2ϩ is not necessary, a low level of Ca 2ϩ (ϳ50 -100 nM) is required for VRAC activation, at least in certain cell types (25,147,155,197). hBest1 has an EC 50 for Ca 2ϩ of ϳ150 nM, which is very close to the permissive level for VRAC activation.…”
Section: B Volume Sensitivity Of Bestrophinssupporting
confidence: 91%
“…This is consistent with previous reports that the activation of VRAC does not require an increase of intracellular Ca 2ϩ (37,77). However, there is considerable evidence that although elevation of Ca 2ϩ is not necessary, a low level of Ca 2ϩ (ϳ50 -100 nM) is required for VRAC activation, at least in certain cell types (25,147,155,197). hBest1 has an EC 50 for Ca 2ϩ of ϳ150 nM, which is very close to the permissive level for VRAC activation.…”
Section: B Volume Sensitivity Of Bestrophinssupporting
confidence: 91%
“…This is consistent with previous reports that the activation of VRAC does not require an increase of intracellular Ca 2+ (Hazama and Okada, 1988;Doroshenko and Neher, 1992). However, there is considerable evidence that although elevation of Ca 2+ is not necessary, a low level of Ca 2+ ‫001-05ف(‬ nM) is required for VRAC activation, at least in certain cell types (Szucs et al, 1996;Nilius et al, 1997;Altamirano et al, 1998;Chen et al, 2007;Park et al, 2007). hBest1 has an EC 50 for Ca 2+ of ‫051ف‬ nM, which is very close to the permissive level for VRAC activation.…”
Section: Similarities and Differences Between Classical Vrac And S2 Vracsupporting
confidence: 91%
“…However, in most cases, GPCR agonist-induced potentiation of intracellular Ca 2þ rise increases the efflux of these osmolytes, an effect that is also mimicked by the use of Ca 2þ -ionophores (Junankar et al, 2002;Mongin andKimelberg, 2002, 2005;Cardin et al, 2003;Loveday et al, 2003;Franco et al, 2004b). These results, together with the observation that a permissive Ca 2þ concentration is necessary for both RVD and the activation of Cl À /organic osmolyte release (Szucs et al, 1996;Mongin et al, 1999;Park et al, 2007), suggest a regulatory role for intracellular Ca 2þ in the activation of these pathways. The mechanisms involved in this phenomenon are still unclear, however, a recent report by Falktoft and Lambert (2004) showed that agonist-induced increase in intracellular Ca 2þ prior to the induction of cell swelling still potentiates RVD and osmolyte efflux, even though the intracellular Ca 2þ concentration has already returned to basal conditions at the moment of the swelling-induced stimulus.…”
Section: Membrane Receptors As Cell Volume Sensorsmentioning
confidence: 84%